This question relates to this post

I tried to verify Eq. (4.2.7) in Polchinski's string theory book vol I p. 127 but I miserably miss a sign

$$ \delta_B (b_A F^A) = i \epsilon (S_2 + S_3) \tag{4.2.7} $$

Necessary equations: $$ S_2 =-iB_A F^A (\phi) \tag{4.2.4}$$ $$ S_3 = b_A c^{\alpha} \delta_{\alpha} F^A(\phi) \tag{4.2.5} $$ $$ \delta_B \phi_i = -i \epsilon c^{\alpha} \delta_{\alpha} \phi_i \tag{4.2.6a} $$ $$ \delta_B B_A=0 \tag{4.2.6b} $$ $$ \delta_B b_A = \epsilon B_A \tag{4.2.6c} $$ $$ \delta_B c^{\alpha} = \frac{i}{2} \epsilon f^{\alpha}_{\beta \gamma} c^{\beta} c^{\gamma} \tag{4.2.6d} $$

My attempt to verify Eq (4.2.7), $$ \delta_B b_A F^A = (\delta_B b_A) F^A + b_A (\delta_B F^A) $$ $$ = \epsilon B_A F^A + b_A (\partial^i F^A) \delta_B \Phi_i = \epsilon B_A F^A + b_A (\partial^i F^A) (-i \epsilon c^{\alpha} \delta_{\alpha} \phi_i) $$ $$ = \epsilon B_A F^A - i \epsilon b_A c^{\alpha} \delta_\alpha F^A = i \epsilon (S_2 - S_3) $$

Why did I get $-S_3$?


I got it. $\epsilon$ anticommutes with $b_A$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.